Dinamika Pelembagaan Agama di Era Digital: Tantangan dan Peluang bagi Warga Nahdlatul Ulama - Balqis Ramadhani Hasani; Argiyanti Nabila Prayana; Wiwik Setiyani (Kartika: Jurnal Studi Keislaman, 2026)
In contemporary religious practice, digital transformation has brought significant changes, particularly within Nahdlatul Ulama Branch Leadership (Pimpinan Ranting) in Plumbungan. This study aims to address several key questions, including how digital media is utilized in the religious activities of NU members, to what extent social media influences religious development, and whether the use of digital media affects traditional religious values. The research employs a qualitative descriptive approach by collecting data through literature studies and online questionnaires. The findings reveal that social media usage is multiplatform and has become an essential component of organizational operations. A total of 76% of respondents stated that social media significantly influences religious development, while all respondents agreed that digital media has been effectively utilized in religious activities. Furthermore, 76% strongly agreed that digital media expands the reach of da’wah, and the majority of respondents (92%) believed that digital media does not diminish traditional religious values. These results indicate that digital media can function as a strategic tool to support da’wah, organizational communication, and the dissemination of religious information without eroding traditional values. However, challenges remain regarding digital literacy and the validity of information